Rasagiline for amyotrophic lateral sclerosis: A randomized, controlled trial. Issue 2 (26th November 2018) - Statland, Jeffrey M.; Moore, Dan; Wang, Yunxia; Walsh, Maureen; Mozaffar, Tahseen; Elman, Lauren; Nations, Sharon P.; Mitsumoto, Hiroshi; Fernandes, J. Americo; Saperstein, David; Hayat, Ghazala; Herbelin, Laura; et al.
ABSTRACT: Introduction : Rasagiline is a monoamine oxidase B (MAO‐B) inhibitor with possible neuroprotective effects in patients with amyotrophic lateral sclerosis (ALS). Methods : We performed a randomized, double‐blind, placebo‐controlled trial of 80 ALS participants with enrichment of the placebo group with historical controls ( n = 177) at 10 centers in the United States. Participants were randomized in a 3:1 ratio to 2 mg/day rasagiline or placebo. The primary outcome was average slope of decline on the ALS Functional Rating Scale—Revised (ALSFRS‐R). Secondary measures included slow vital capacity, survival, mitochondrial and molecular biomarkers, and adverse‐event reporting. Results : There was no difference in the average 12‐month ALSFRS‐R slope between rasagiline and the mixed placebo and historical control cohorts. Rasagiline did not show signs of drug‐target engagement in urine and blood biomarkers. Rasagiline was well tolerated with no serious adverse events. Discussion : Rasagiline did not alter disease progression compared with controls over 12 months of treatment. Muscle Nerve 59 :201–207, 2019